Metastatic insulinoma presenting 14 years after benign tumour resection: a rare case and management dilemma. (23rd September 2020) - Keen, F; Iqbal, F; Owen, P; Christian, A; Kumar, N; Kalhan, A
Abstract : Summary: We present a 60-year-old woman who underwent successful surgical resection (partial pancreatectomy) for a low grade non-functioning pancreatic neuroendocrine tumour (pNET), with no biochemical or radiological features of recurrence on follow-up visits for 5 years. Fourteen years after the initial surgery, she developed spontaneous severe hypoglycaemic episodes which required hospitalisation, with subsequent investigations confirming the diagnosis of a metastatic insulin-secreting pNET (insulinoma). Medical management of her severe spontaneous hypoglycaemic episodes remained challenging, despite optimum use of diazoxide and somatostatin analogue therapy. Based on a discussion at the regional neuroendocrine tumour multidisciplinary team meeting, she underwent an elective hepatic trans-arterial embolization which was unfortunately unsuccessful. She ended up requiring an emergency right hemihepatectomy and left retroperitoneal mass resection which finally stabilised her clinical condition. Learning points: Ours is only the seventh case report of a previously benign pNET presenting as a functional insulin secreting metastatic tumour. However, it is the first case report, in which the metastatic functional pNET presented after such a long hiatus (14 years). There is currently no clear consensus regarding the length of follow-up of non-functional pNET which are deemed cured post-surgical resection, with most guidelines advocating a median follow up of 5 years (1 ). The delayed presentation in our case suggests additional considerations should be made regarding optimal post-operative surveillance duration based on the age of the patient, location of the tumour, lymph node spread and Ki-67 index. Hepatic artery embolization and/or partial hepatectomy remains a treatment option for pNET patients with significant hepatic metastasis.